The Efficacy of Chaihu-Guizhi-Ganjiang Decoction on Chronic Non-Atrophic Gastritis with Gallbladder Heat and Spleen Cold Syndrome and Its Metabolomic Analysis: An Observational Controlled Before-After Clinical Trial - Wen T; Liu X; Pang T; Li M; Jiao G; Fan X; Tang J; Zhang C; Wang Z; Yue X; Chen W; Zhang F (Dove Medical Press, 2024)
Tao Wen,1,* Xuan Liu,2,* Tao Pang,1,* Mingming Li,1 Guangyang Jiao,3 Xiangcheng Fan,1 Jigui Tang,4 Ci'an Zhang,4 Zhipeng Wang,1 Xiaoqiang Yue,4,* Wansheng Chen,1,3,5 Feng Zhang1,5 1Department of Pharmacy, Changzheng Hospital, Naval Medical University, Shanghai, People's Republic of China; 2Oncology-Department, Shanghai Guanghua Hospital of Integrative Medicine, Shanghai, People's Republic of China; 3The SATCM Key Laboratory for New Resources & Quality Evaluation of Chinese Medicine, Institute of Chinese Materia Medica, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 4Department of Traditional Chinese Medicine, Changzheng Hospital, Naval Medical University, Shanghai, People's Republic of China; 5Shanghai Key Laboratory for Pharmaceutical Metabolite Research, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Feng Zhang; Wansheng Chen, Changzheng Hospital, Naval Medical University, No. 415, Fengyang Road, Shanghai, 200003, People's Republic of China, Email fengzhang@smmu.edu.cn; chenwansheng@smmu.edu.cnPurpose: The aim of this study was to verify the effectiveness and explore the mechanism of Chaihu-Guizhi-Ganjiang decoction (CGGD) in the treatment of chronic non-atrophic gastritis (CNAG) with gallbladder heat and spleen cold syndrome (GHSC) by metabolomics based on UHPLC-Q-TOF/MS.Patients and Methods: An observational controlled before-after study was conducted to verify the effectiveness of CGGD in the treatment of CNAG with GHSC from January to June 2023, enrolling 27 patients, who took CGGD for 28 days. 30 healthy volunteers were enrolled as the controls. The efficacy was evaluated by comparing the traditional Chinese medicine (TCM) syndrome and CNAG scores, and clinical parameters before and after treatment. The plasma levels of hormones related to gastrointestinal function were collected by ELISA. The mechanisms of CGGD in the treatment of CNAG with GHSC were explored using a metabolomic approach based on UHPLC-Q-TOF/MS.Results: Patients treated with CGGD experienced a statistically significant improvement in TCM syndrome and CNAG scores (p < 0.01). CGGD treatment evoked the concentration alteration of 15 biomarkers, which were enriched in the glycerophospholipid metabolism, and branched-chain amino acids biosynthesis pathways. Moreover, CGGD treatment attenuated the abnormalities of the gastrointestinal hormone levels and significantly increased the pepsinogen level.Conclusion: It was the first time that this clinical trial presented detailed data on the clinical parameters that demonstrated the effectiveness of CGGD in the treatment of CNAG with GHSC patients. This study also provided supportive evidence that CNAG with GHSC patients were associated with disturbed branched-chain amino acid metabolism and glycerophospholipid levels, suggesting that CNAG treatment based on TCM syndrome scores was reasonable and also provided a potential pharmacological mechanism of action of CGGD. Keywords: traditional Chinese medicine, chronic gastritis, metabolomics, branched-chain amino acid, glycerophospholipid